Peran Kepala Sekolah Sebagai Supervisor Untuk Meningkatkan Kompetensi Pedagogik Guru SD di Gugus I Kecamatan Aesesa Kabupaten Nagekeo - Benedikta Boleng (JURNAL ASIMILASI PENDIDIKAN, 2025)
This research aims to analyze the role of school principals as supervisors in improving the pedagogical competence of elementary school teachers in Cluster I, Aesesa District, Nagekeo Regency. The approach used in this research is a qualitative approach. The methods used in this research are interviews, observation and documentation. The results of the research show that the role played by the Principal as a supervisor in improving the pedagogical competence of elementary school teachers in Cluster I, Aesesa District, Nagekeo Regency is conducting classroom visits; conduct observation visits; guiding teachers on ways to study students' personalities and/or overcome problems experienced by students; guiding teachers in matters related to the implementation of the school curriculum; holding meetings or meetings; holding group discussions; and holding in-service training. The factors that support the role of the principal in carrying out his function as a supervisor are the existence of regulations regarding teacher discipline and teacher performance. Meanwhile, several inhibiting factors include a lack of discipline from teachers; lack of financial support and the curriculum for teaching and learning activities has not been fully implemented.